The Contribution of Achievement Motivation, Use of Information Technology, and Learning Outcomes of Creative Entrepreneurial Products on Interest in Entrepreneurship - Fitri Jalal; Muhammad Adri; Riki Mukhaiyar; Rajal Abdullah (JETL (Journal of Education, Teaching and Learning), 2025)
Entrepreneurship education in vocational high schools plays a crucial role in shaping students to become independent and innovative individuals capable of creating their own businesses. However, many students still show a low level of interest in entrepreneurship, which calls for an investigation into the influencing factors. This study aims to analyze the influence of achievement motivation and the use of information technology on students’ entrepreneurial interest, either directly or indirectly through entrepreneurial learning outcomes. The research was conducted using a quantitative correlational method involving 125 students from SMKN 2 Merangin during the 2024/2025 academic year. Data were collected through validated and reliable questionnaires measuring achievement motivation, technology use, and entrepreneurial interest. Students' learning outcomes were obtained from their average scores in the subject "Productive Creative Entrepreneurship." Data were analyzed using descriptive statistics, regression analysis, and path analysis with the help of RStudio. The results showed that both achievement motivation and information technology use had a significant positive effect on students’ entrepreneurial learning outcomes and their interest in entrepreneurship. Specifically, learning outcomes acted as a mediating variable, enhancing the influence of both independent variables on entrepreneurial interest. The path analysis indicated that the total effects of achievement motivation and technology use on entrepreneurial interest were 0.31 and 0.29, respectively, with a direct contribution from learning outcomes of 0.32. In conclusion, achievement motivation and the use of information technology significantly influence students’ entrepreneurial interest, with entrepreneurial learning outcomes serving as an important mediating factor. These findings suggest that strengthening motivation and integrating digital literacy into the curriculum can enhance students' readiness and enthusiasm for entrepreneurship